Sosialisasi Pengenalan Manajemen SDM Kreatif Berbasis Teknologi Digital - Sarlota Ratang; Herlina Mulyono; Elsyan Marlissa (Program Studi Ekonomi Pembangunan, 2025)
The rapid development of information and communication technology (ICT) has significantly transformed human resource (HR) management, including among youth entrepreneurship communitEies in Jayapura. However, the adoption of digital tools for HR management remains limited due to a lack of technical skills and access to training. This community engagement program aimed to enhance the capacity of youth at Ebenhaezer Church, Jayapura, in managing business teams creatively and efficiently through digital-based HR training. The program was implemented in four phases: preparation, interactive training, independent practice, and evaluation. Participants were trained to use digital tools such as Trello, Google Workspace, and Notion to form team structures, design SOPs, and develop business plans. The results showed a 45% improvement in participants’ understanding (post-test), the formation of five creative business groups, and the development of concrete business prototypes. This program successfully equipped youth with collaborative and digital-based HR management skills, contributing to the development of an innovative and competitive local small business ecosystem